Penentuan Kondisi Pelarutan Residu dari Hasil Pelarutan Parsial Monasit Bangka - Sumarni, Sumarni; Prassanti, Riesna; Trinopiawan, Kurnia; Sumiarti, Sumiarti; Nuri, Hafni Lissa (EKSPLORIUM, 2011)
Bangka monazite processing to separate its major elements i.e. phosphate (PO4), rare earth (RE), uranium (U) and thorium (Th) through decomposition prosess with NaOH to separate the PO4 first. This prosess produces a residue of (U, Th, RE) hydroxide. Then this residue is dissolved with HCl concentrate partially at 3,7 of pH to separate the RE from U and Th. In this process 62 % of RE is dissolved. The residue of RE dissolution at 3,7 of pH still contain U, Th and RE, so continuation research needed to be done separate U, Th and RE mentioned. The purpose of this research is to determine the optimum condition of residue dissolution as product of partiel dissolution by using concentrate H2SO4. On the next research each element of U, Th and RE will be separated. The research’s parameters are dissolution time, dissolution temperature and consumption of H2SO4. The result showed that the optimum conditions were 2 hours of time, 30 oC of temperature and 100 ml of H2SO4/gram of feed with recovery 92,30 % of U, 97,15 % of Th and 93,46 % of RE.